Over the hedge - Johnson, Tim, 1961 Aug. 27-; Kirkpatrick, Karey; Willis, Bruce, 1955-; Shandling, Garry; Syke, Wanda, 1964-; Fry, Michael, 1959-; Lewis, T., (Thomas) (Burbank, CA : DreamWorks Home Entertainment, 2006)
As a group of forest animals end their hibernation they learn their forest home has become a suburb filled with humans.
Based on the comic strip by Michael Fry and T Lewis.
Originally released as a motion picture in 2006.
Features: Dwayne's verm-tech infomercial, insider's look behind the hedge, games and activities featurettes.
Bruce Willis, Garry Shandling, Wanda Sykes.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
Keywords: Fry, Michael, -- 1959- -- Film and video adaptations; Lewis, T. -- Film and video adaptations; Animals -- Drama; Habitat (Ecology) -- Drama; Cities and towns -- Growth -- Drama; Suburbs -- Drama; Video recordings for the hearing impaired; Based on the book; Feature films; Animated films